Frequent sleep‐related bitemporal focal seizures in transient epileptic amnesia syndrome: Evidence from ictal video‐EEG. Issue 2 (7th February 2017) - Burkholder, David B.; Jones, Amy L.; Jones, David T.; Fabris, Rachel R.; Britton, Jeffrey W.; Lagerlund, Terrence D.; So, Elson L.; Cascino, Gregory D.; Worrell, Gregory A.; Shin, Cheolsu; St. Louis, Erik K.
Summary: Two patients who shared similar presenting clinical features of anterograde and retrograde autobiographical amnesia typical of transient epileptic amnesia (TEA) underwent prolonged video electroencephalogram (VEEG) monitoring and were found to have sleep‐activated epileptiform activity and frequent subclinical bitemporal seizures predominantly during sleep. Case 1 is a 59‐year‐old woman whose presenting complaint was memory impairment. Over 18 months, she had three distinct 8‐h‐long episodes of confusion and disorientation with persistent anterograde and retrograde autobiographical amnesia. VEEG recorded frequent interictal bitemporal sharp waves confined to sleep, and 14 subclinical seizures, also mostly during sleep. Case 2 is a 50‐year‐old woman with known focal epilepsy also presented with memory complaints. Over the course of 1 year, she had two discrete 2‐h‐long episodes of amnesia, with ongoing anterograde and retrograde autobiographical amnesia. VEEG recorded independent bitemporal sharp waves, and 14 subclinical seizures during sleep and drowsiness. Memory impairment improved in both patients with successful treatment of their seizures. Although the etiology of accelerated long‐term forgetting (ALF) and remote memory impairment (RMI) in transient epileptic amnesia (TEA) is unknown, these cases suggest frequent sleep‐related seizures may contribute, and they highlight the importance of video‐EEG monitoring.